Understanding the Interrelationship Between Career and Professional Development and Job Satisfaction (Jurnal Manajemen Bisnis, 2021)
Career and professional development is a long process of personal growth along an individual’s life span. Despite their efforts to develop skills and knowledge, there are extrinsic factors that are expected by the employees to help advance their careers. There are also some factors make individuals opt to stay at their current positions and feel satisfied with the jobs. To maintain a healthy workplace environment, a Global Staff Survey (GSS) was conducted by a non-profit organization in 2020. Out of 12 topics surveyed, this article aims to analyze the result of the survey, particularly, Indonesia-specific country-context, focusing on understanding the interrelationship between career and professional development and job satisfaction or motivation. Primary data is taken from the survey participated by 192 respondents from six provinces in Indonesia. The respondents consist of different levels of positions of both national and international staff with various lengths of employment. Career and Professional Development and Job Satisfaction/Motivation are two variables extracted from the result of the survey which is analyzed through desk review methodology.